Improving Critical Thinking Skills by Applying the Power of two Model in Elementary School Students - Radina Alfira Pratiwi; Iis Aprinawati; Fadhilaturrahmi Fadhilaturrahmi; Yenni Fitra Surya; Mohammad Fauziddin (Universitas Muhammadiyah Enrekang, 2022)
This study aims to improve the critical thinking skills of fifth grade students at SD 013 Kumantan for the 2022/2023 academic year, which consists of 10 students. The research method is centered on Classroom Action Research (PTK) which is carried out in two learning cycles. Each cycle consists of two meetings and four learning stages, namely: planning, implementing, observing, and reflecting. When the research was carried out in August 2022. Data collection techniques were in the form of documentation, observation and tests. The results of the critical thinking skills of fifth grade students at SDN 013 Kumantan in pre-action with a learning completeness percentage of 30%. In the first cycle the first meeting with a learning completeness percentage of 30% and in the first cycle the second meeting experienced an increase with a learning completeness percentage of 40%. In the second cycle, the first meeting also increased with a learning mastery percentage of 60%, and in the second cycle, the second meeting experienced another increase with a 90% learning completeness percentage. Thus it can be concluded that the application of The Power Of Two learning model can improve the critical thinking skills of fifth grade students at SDN 013 Kumantan. Keywords : The Power Of Two Learning Model, Critical Thinking Skills, and Elementary School.